Pleurer les victimes du scandale de Panama ou subvertir les institutions ? - Jean-Yves Mollier (Criminocorpus)
After recalling the context in which the sidewalk literature of the years 1885-1900, the Boulangist Crisis, the Panama Scandal and the Dreyfus Case unfolded, this article examines more specifically the complaints linked to the collapse of the Universal Company of the Inter-Oceanic Canal. Although not all the songs produced in 1892-1893 are related to the lament genre, many of them are part of it, the victims being either the small savers who were robbed or the people, the true recipients of this particularly poisonous form of propaganda. Anti-Semitism and anti-parliamentarianism are the two main ingredients, the aim being the subversion of institutions and the overthrow of the republican regime.